FEATURES OF FINANCIAL PLANNING OF PRODUCTIONS ON THE ENTERPRISES OF MECHANICAL ENGINEERING - S. Demin (Publishing House of the State University of Management, 2016)
In the article it is proved that one of the most important tasks for the enterprises of mechanical engineering at the present stage is improvement of system of financial planning. At the same time the strong financial position of the enterprise is the main criterion of efficiency of functioning of system of budgeting of a production activity. The algorithm of reforming of system of distribution of financial resources of the enterprises is offered. The main stages of the budgetary cycle, and also sequence and content of the budgetary management are considered.